2000
DOI: 10.1177/002076400004600105
|View full text |Cite
|
Sign up to set email alerts
|

The Ethnic Density Effect: Results From a National Community Survey of England and Wales

Abstract: Using data from a community survey of 5196 ethnic minority and 2867 white respondents, together with data on local group concentration from the 1991 Census, the hypothesis was tested that ethnic group concentration is associated with lower levels of reported psychiatric symptoms. The hypothesis was broadly confirmed, both for within- and between-group differences. However, the effect was found to be modest in size and in one group, the Pakistani sample, was reversed. The findings are inconsistent with an expla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
189
5
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(204 citation statements)
references
References 17 publications
(14 reference statements)
8
189
5
2
Order By: Relevance
“…In addition, age and marital status appeared to have effects on the prevalence across the ethnicity. This finding was consistent with previous study on ethnic density hypothesis which proposed that persons who live in neighbourhood with a greater proportion of residents of their own race or ethnicity have better mental health outcomes and lower levels of depression symptoms than persons who live in neighbourhood members with few people of their own race/ethnicity [16]. A review by Shaw et al [15] showed consistent finding of the protecttion of ethnic density on depression and anxiety.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, age and marital status appeared to have effects on the prevalence across the ethnicity. This finding was consistent with previous study on ethnic density hypothesis which proposed that persons who live in neighbourhood with a greater proportion of residents of their own race or ethnicity have better mental health outcomes and lower levels of depression symptoms than persons who live in neighbourhood members with few people of their own race/ethnicity [16]. A review by Shaw et al [15] showed consistent finding of the protecttion of ethnic density on depression and anxiety.…”
Section: Discussionsupporting
confidence: 91%
“…They showed that the ethnic density had protective association on suicide and self harm as well as on psychosis [15]. In a large community study in England and Wales [16], 5167 ethnic minority and 2867 white were studied. The protective effects of ethnic density on psychiatric morbidity were also observed.…”
Section: Introductionmentioning
confidence: 99%
“…One body of research has focused on variations in risk of adverse health outcomes in minority groups with respect to their relative size or density locally, an example of ecological effect modification. Several studies have suggested that the risk of mental illness and suicide varies inversely with ethnic density in local areas (Wechsler and Pugh 1967, Rabkin 1979, Halpern 1993, Neeleman and Wessely 1999, Halpern and Nazroo 2000. The literature on psychological adjustment provides similar findings.…”
Section: Problematic Conceptsmentioning
confidence: 80%
“…10,11 However, these hypotheses have not been formally tested within this ethnic group as there has been little research into perinatal depression among black women in the UK. Increasing evidence of the deleterious consequences of perinatal depression for women's life-long mental health as well as the physical, cognitive, emotional, and psychological development and wellbeing of their children suggests that this is a serious omission.…”
Section: Resultsmentioning
confidence: 99%